B2B Inventory Management : A Lean Management Approach - Avi, Arnav; Martínez, Felipe; Jirsák, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This Bachelor thesis aims to show inventory management methods and their improvements in a warehouse. It comes after the literature review of Lean management in a warehouse with a focus on business-to-business inventory management. The analysis is conducted using TIMWOODS waste classification and further research through the FMEA method, which is used to rate issues on three parameters severity, occurrence and detection, these will be used to assess inventory management and other issues faced by the warehouse and company in question. The aim and outcome of the bachelor thesis is to employ lean management in a business-to-business firm and provide possible solutions to improve the activities in a business- to-business warehouse based on the Lean Waste Analysis Number.
Vedoucí práce: Felipe Martínez
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses